Anxiety Treatment and Targeted Sleep Enhancement to Address Sleep Disturbance in Pre/Early Adolescents with Anxiety. (29th March 2019) - McMakin, Dana L.; Ricketts, Emily J.; Forbes, Erika E.; Silk, Jennifer S.; Ladouceur, Cecile D.; Siegle, Greg J.; Milbert, Melissa; Trubnick, Laura; Cousins, Jennifer C.; Ryan, Neal D.; Harvey, Allison G.; Dahl, Ronald E.
Abstract : Sleep disturbance is prevalent in anxious youth and prospectively predicts poor emotional adjustment in adolescence. Study 1 examined whether anxiety treatment improves subjective and objective sleep disturbance in anxious youth. Study 2 examined whether a sleep intervention called Sleeping TIGERS can further improve sleep following anxiety treatment. Study 1 examined 133 youth (ages 9–14; 56% female; 11% ethnic/racial minority) with generalized, social, or separation anxiety over the course of anxiety treatment (cognitive behavioral treatment or client-centered treatment). Sleep-related problems (parent-, child-report) and subjective (diary) and objective (actigraphy) sleep patterns were assessed across treatment in an open trial design. Study 2 included 50 youth (ages 9–14; 68% female; 10% ethnic/racial minority) who continued to report sleep-related problems after anxiety treatment and enrolled in an open trial of Sleeping TIGERS. Pre- and postassessments duplicated Study 1 and included the Focal Interview of Sleep to assess sleep disturbance. Study 1 demonstrated small reductions in sleep problems and improvements in subjective sleep patterns (diary) across anxiety treatment, but outcomes were not deemed clinically significant, and 75% of youth stayed above clinical cutoff. Study 2 showed clinically significant, large reductions in sleep problems and small changes in some subjective sleep patterns (diary). Anxiety treatment improves, but does not resolve, sleep disturbance in peri-pubertal youth, which may portend risk for poor emotional adjustment and mental health. The open trial provides preliminary support that Sleeping TIGERS can improve sleep in anxious youth to a clinically significant degree.